Association of risk of malnutrition with adverse outcomes and early support on discharge in acute stroke patients without prestroke disability: A multicenter, registry‐based cohort study. (19th October 2021) - Fluck, David; Fry, Christopher H.; Gulli, Giosue; Affley, Brendan; Robin, Jonathan; Kakar, Puneet; Sharma, Pankaj; Han, Thang S.
Abstract: Background: Malnutrition in hospitals remains highly prevalent. As part of quality improvement initiatives, the Royal College of Physicians recommends nutrition screening for all patients admitted with acute stroke. We aimed to examine the associations of patients at risk of malnutrition with poststroke outcomes. Methods: We analyzed prospectively collected data from four hyperacute stroke units (HASUs) (2014–2016). Nutrition status was screened in 2962 acute stroke patients without prestroke disability (1515 men, [mean ± SD] 73.5 years ± 13.1; 1447 women, 79.2 ± 13.0 years). The risk of malnutrition was tested against stroke outcomes and adjusted for age, sex, and comorbidities. Results: Risk of malnutrition was identified in 25.8% of patients). Compared with well‐nourished patients, those at risk of malnutrition had, within 7 days of admission, increased risk of stay on the HASU of >14 days (odds ratio [OR]: 9.9 [7.3–11.5]), disability on discharge (OR: 8.1 [6.6–10.0]), worst level of consciousness in the first 7 days (score ≥ 1) (OR: 7.5 [6.1–9.3]), mortality (OR: 5.2 [4.0–6.6], pneumonia (OR: 5.1 [3.9–6.7]), and urinary tract infection (OR: 1.5 [1.1–2.0]). They also required palliative care (OR: 12.3 [8.5–17.8]), discharge to new care home (OR: 3.07 [2.18–4.3]), activities of daily living support (OR: 1.8 [1.5–2.3]), planned joint care (OR: 1.5 [1.2–1.8]), and weekly visits (OR: 1.4 [1.1–1.8]). Conclusion: Patients at risk of malnutrition more commonly have multiple adverse outcomes after acute stroke and greater need for early support on discharge.